1993
DOI: 10.1002/ajmg.1320470320
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Detection of epidermolysis bullosa letalis with pyloric atresia in a fetus by abnormal ultrasound and elevated alpha‐fetoprotein

Abstract: We report on the prenatal diagnosis of epidermolysis bullosa letalis with pyloric atresia in a pregnancy not known to be at risk for this condition. Elevated maternal serum alpha-fetoprotein levels led to ultrasonography which demonstrated gastric dilatation, consistent with pyloric atresia, and echogenic particles in the amniotic fluid, the "snowflake sign," previously described in two pregnancies of fetuses with disorders of skin sloughing. Amniotic fluid alpha-fetoprotein was markedly elevated and the acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…The synthesis of AFP has further been reported in neonatal rat skin implants (Mujoo et al, 1983), but has yet to be confirmed. The elevated AFP levels reported in infants with functional and dystrophic epidermolysis bullosa, aplasia cutis congenita, and epidermolysis bullosa letalis (Dolan et al, 1993;Drugan et al, 1995;Gerber et al, 1995) attest to a possible linkage between AFP and skin intermediate filaments. In fact, it has been suggested that AFP screening would obviate the need for fetal skin sampling in the prenatal diagnosis of these disorders (Gerber et al, 1995).…”
Section: J) Amino Acid-rich Repeat Sitesmentioning
confidence: 87%
“…The synthesis of AFP has further been reported in neonatal rat skin implants (Mujoo et al, 1983), but has yet to be confirmed. The elevated AFP levels reported in infants with functional and dystrophic epidermolysis bullosa, aplasia cutis congenita, and epidermolysis bullosa letalis (Dolan et al, 1993;Drugan et al, 1995;Gerber et al, 1995) attest to a possible linkage between AFP and skin intermediate filaments. In fact, it has been suggested that AFP screening would obviate the need for fetal skin sampling in the prenatal diagnosis of these disorders (Gerber et al, 1995).…”
Section: J) Amino Acid-rich Repeat Sitesmentioning
confidence: 87%
“…The coexistence of pyloric atresia and junctional epidermolysis bullosa has been repeatedly observed (Korber and Glasson, 1977;Cowton et al, 1982;Achiron et al, 1992;Lestringant et al, 1992;Dolan et al, 1993;Valari et al, 1995;Shaw et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…It was even thought that sonographic signs were suggestive of the PA-JEB syndrome. A review of the literature was undertaken and reinforced our conviction that the fetus was affected with PA-JEB (Achiron et al, 1992;Dolan et al, 1993;Weissman et al, 1994). When informed of the extreme severity of the disease, the parents agreed to a fetal skin biopsy which they had at ®rst turned down.…”
Section: Ultrasound Examinationmentioning
confidence: 98%
See 1 more Smart Citation
“…The amniotic fluid (AF) of such fetuses contained high levels of acetylcholinesterase (Ache) enzyme, however, the karyotype was normal. Some fetuses further displayed mutated integrin-alpha-6 and B4 genes, kidney malformations, hypoplastic or absent hemi-desmosomes along the dermal-epidermal junction, and aplasia cutis congenital [47,48]. Fetal skin biopsies are usually performed but can produce false positive results unless electron microscopic examination is available.…”
Section: Afp and Inflammation During Pregnancymentioning
confidence: 99%